O Pomiarach Odkształceń Wewnątrz Elementów Betonowych - Brandt, A.; Jendo, S. (Engineering Transactions, 1965)
The paper represents measurement results of strain inside a concrete cylinder of 16 cm in dia., 50 cm high, subjected to axial load. The measurement was performed by means of a three-dimensional set of resistance strain gauges included in the cylinder, The indications of the strain gauges enable the determination of all the six components of the strain tensor. The measurement results are represented in the form of diagrams of the strain components in function of the load, for various ages of the concrete. The diagrams of the distortions, which have not yet been investigated, show that these quantities are different from zero in the case of axial load applied with engineering accuracy.